The science of sport sprinting - Platt, Geoffrey K. Dr
The Science of Sports: Sprinting examines the scientific principles that underpin the preparation and performance of athletes at all levels, from grassroots to Olympic competition. Drawing on the expertise of some of the world's leading coaches and sport science professionals, this book presents a detailed analysis of the latest evidence and explores the ways in which science has influenced, and subsequently improved, the sport of sprinting. The Science of Sport series is essential reading for students and academics, coaches and performers, physiotherapists, club doctors and professional support staff working in the sport. key topics covered include: Talent identification and youth development; Biomechanics; Performance analysis; Coaching and coach education; Training methods; Fitness testing; Nutrition; Mental skills; Incidence and treatment of injuries; Performance lifestyle.